2001
DOI: 10.1103/physrevc.63.044007
|View full text |Cite
|
Sign up to set email alerts
|

Parity-violating electron-deuteron scattering

Abstract: The longitudinal asymmetry due to Z 0 exchange is calculated in quasi-elastic electron-deuteron scattering at momentum transfers |Q 2 | ≃ 0.1 GeV 2 relevant for the SAMPLE experiment. The deuteron and pn scattering-state wave functions are obtained from solutions of a Schrödinger equation with the Argonne v 18 potential. Electromagnetic and weak neutral one-and two-nucleon currents are included in the calculation. The two-nucleon currents of pion range are shown to be identical to those derived in Chiral Pertu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Note that in Ref. [31] the relativistic corrections in j 5 i and twobody axial currents were neglected, in line with the expectation, confirmed in the present study, that the associated contributions were small. Finally, the neutral weak currents given above are at tree-level, electro-weak radiative corrections as well as strange-quark contributions to the vector and axial-vector currents [30] have been ignored.…”
Section: B Neutral Weak Currentssupporting
confidence: 76%
See 2 more Smart Citations
“…Note that in Ref. [31] the relativistic corrections in j 5 i and twobody axial currents were neglected, in line with the expectation, confirmed in the present study, that the associated contributions were small. Finally, the neutral weak currents given above are at tree-level, electro-weak radiative corrections as well as strange-quark contributions to the vector and axial-vector currents [30] have been ignored.…”
Section: B Neutral Weak Currentssupporting
confidence: 76%
“…[31], where it was shown that twobody terms in the nuclear electromagnetic and weak neutral currents only produce (1-2)% corrections to the asymmetry due to the corresponding single-nucleon currents. The present study-a short account of which has been published in Ref.…”
Section: Deuteron Electro-disintegration At Quasi-elastic Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear corrections can potentially modify the asymmetry, both through parity-conserving [ 15], and parity-violating [ 16,17] two-body effects. At the SAMPLE kinematics the PC terms modify the asymmetry by 1-3%, and the PV terms are negligible.…”
Section: Sample At Mit-batesmentioning
confidence: 99%
“…The quasi-elastic deuterium asymmetry is dependent upon both the momentum and the energy transfer and is modified by nucleon-nucleon interaction effects. The coefficients were determined using a calculation provided by R. Schiavilla [Sch06,SCP04] in which he used the AV18 nucleon-nucleon interaction model as described in [DSvK01]. The calculation included lowest-order relativistic corrections to the one-body electromagnetic and weak currents.…”
Section: Calculation Of the Deuterium Coefficients Is Not As Straightmentioning
confidence: 99%